The Role of School Principal Leadership Style, Work Environment and Family Support on PAUD Teacher Performance - Safrida Safrida; Ronald Maraden Parlindungan Silalahi; Hendy Tannady (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Teacher performance is an important part of achieving the goals of an educational institution. The good or bad of an educational institution or school can also be seen from the level of teacher performance. To avoid the bad side of teacher performance, a comfortable work environment, the right leadership style and support from the family are needed so that performance can be more optimal. This research intends to analyze the performance of teachers in PAUD in Cengkareng District, West Jakarta, which is affected by the work environment, leadership style and family support. Questionnaire data as primary data and school IKP and EKI documents as secondary data. There were 22 respondents in this research who were sampled. Multiple linear regression analysis as data analysis and t-test as a hypothesis test were all processed through SPSS version 26. The results of this research describe that performance is not partially affected by the work environment. Meanwhile performance is significantly affected positively by leadership style. Furthermore, performance is significantly positively affected by family support. Other test results, performance is significantly positively affected by the work environment, leadership style and family support simultaneously.